Ratio Decidendi Putusan, Jenis-Jenis Putusan dan Upaya Hukum Terhadap Putusan yang Telah Memiliki Kekuatan Hukum Tetap Ditinjau dari Perspektif Hukum Acara Pidana di Indonesia - Ghoniyah Zulindah Maulidya; Syahdila Nur Rahmawati; Vina Rahmawati; Alifian Fahdzan Mardany (Fakultas Ilmu Sosial dan Humaniora, 2023)
This journal that we compiled certainly has a purpose, namely to know and understand court decisions, types of judges' decisions. This journal will of course describe and explain what our goals are. We have compiled this journal based on literature study research methods with an approach through journals, law and the Code of Criminal Procedure relating to the purpose of this journal. The results of this journal research show that the verdict itself has a definition, namely a decision from the court in a lawsuit based on a dispute or based on a dispute. Furthermore, regarding the judge's decision. The judge's decision is a statement from the judge himself, where the judge is a state official. Who has the authority to give a decision on a case. As for each decision there are 3 possibilities including the imposition of a criminal, an acquittal and a acquittal decision. it talks about the types of judge's decisions including final decisions that are material and decisions that are not final decisions. In addition, in binding legal force there are ordinary legal remedies (resistance, appeal, cassation) and extraordinary legal remedies (examination of the level of cassation and review). For the implementation of the judge's decision, it is regulated in the Criminal Procedure Code Article 270-276. In litigation in court there are court costs, among others, if the convict is convicted of one case from 1 person, the costs will be borne together in a balanced manner. in chapters 277-283.